The Attitudes of 11 th graders towards some aspects of the curriculum physics (A Field Study in Lattakia ) - نصور, رغداء; خضرو, أحمد; خريما, ميساء (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The study aims to explore students attitudes, at The 11th towards some sides of curriculum physics in Lattakia city. The sample selected randomly, contain(160) students(2020-2021), The researcher used a questionnaire that consists of three basic areas:the shape of the booth and its design, the content, and the evaluation . The researcher depended on the descriptive approach. After which analyzed the result using program(spss) EMI. The research suggests: modifying the physics curriculum to keep pace with the cultural development and interest in printing books without mistakes typographical and benefit from the methods of modern education.and heedfulness direction art for books, figuration watchdogs canvass the books and its calendar from away ministry.